2023
DOI: 10.3390/ijerph20064837
|View full text |Cite
|
Sign up to set email alerts
|

Distress following the COVID-19 Pandemic among Schools’ Stakeholders: Psychosocial Aspects and Communication

Abstract: In response to the COVID-19 pandemic, many governments ordered school closures as a containment measure, with Israel being among over 100 countries to do so. This resulted in the abrupt shift to online and remote education for many students. Despite attempts to minimize the effects of disrupted education and create a dynamic virtual learning environment, the literature highlights various challenges including lack of communication with implications of distress faced by key stakeholders (students and their paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In our earlier research using the same dataset (Kaim et al, 2023), we explored the perceived levels of communication and psychosocial aspects among high school students, parents, teachers, and principals during both distance and frontal learning in the Israeli education system. The results highlighted significant consequences of distance learning on communication and psychosocial aspects, resulting in enduring long-term distress, especially among students.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our earlier research using the same dataset (Kaim et al, 2023), we explored the perceived levels of communication and psychosocial aspects among high school students, parents, teachers, and principals during both distance and frontal learning in the Israeli education system. The results highlighted significant consequences of distance learning on communication and psychosocial aspects, resulting in enduring long-term distress, especially among students.…”
Section: Discussionmentioning
confidence: 99%
“…After the final development of the tool, it was distributed crosssectionally in October-November 2022, approximately two and a half years following the initial closure of in-person learning in the Israeli school system on March 15, 2022. The research enlisted a comprehensive group of 1802 individuals, encompassing the primary stakeholders in the education system: 1000 students in grades 10 through 12, 301 parents, 449 teachers, and 52 principals, all hailing from 890 high schools within the Israeli Jewish community (Kaim et al, 2023). This sample dataset is the same as in the earlier research conducted and reported in Kaim et al (2023).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations